Semiotic Analysis of Tapis Tuho Cloth (Old Tapis) as Lampung Ceremonial Clothing - Evangeline Jeanette Liem; Elizabeth Susanti (LPPM Universitas Bumigora Mataram, 2024)
Tapis Tuho cloth is one of the Tapis cloths usually worn as traditional Lampung ceremonial clothing. Tapis Tuho cloth is worn by people with high social status. This study aims to analyse the Tapis Tuho cloth semiotically and also to understand the meaning of its motifs and colors. The method of this study was carried out using semiotic analysis theory and qualitative descriptive methods. The novelty of this analysis and research results is that the motifs (Aro tree motif, riding animal motif, dragon motif, sasab motif, swinging crown motif, zig-zag pattern) and colors (red, black, gold) on the Tapis Tuho cloth are not only decorative but have meaning according to the use of the Tapis Tuho cloth used for Lampung traditional ceremonies. The implication of this study is that the Indonesian people, especially the people of Lampung, can better understand the meaning of the motifs and colors on the Tapis Tuho cloth, and preserve the traditional cultural heritage of Lampung, so that it can be passed on from generation to generation, both in terms of the meaning and existence of the cloth.